UJI CITA RASA KOPI LOKAL ROBUSTA (Coffea canephone) FERMENTASI GUNUNG SINDORO, GUNUNG SUMBING, DAN ROWO SENENG - Deni; Widata, Sri; Arnanto, Driska (LENVARI, 2025)
The research aims to determine the results of the taste test of local robusta coffee fermented from Mount Sindoro, Mount Sumbing, and Rowo Seneng. This research was conducted from 19 September to 31 October 2024, to carry out organoleptic tests. This research was carried out in the Integrated Laboratory of Bachelorwiyata Tamansiswa University, Yogyakarta. This research method uses a factorial Complete Randomized Block Design (RAKL), where the first factor is the origin of the Robusta Coffee (Mount Sindoro, Mount Sumbing, and Rowo Seneng) and the second factor is the fermentation time (2 weeks, 3 weeks and 4 weeks). Organoleptic data were analyzed using analysis of variance (ANOVA), while Robusta coffee was evaluated through a hedonic sensory test using a hedonic scale from 1 (not liked) to 5 (very liked). The results of the research show that there is a difference in gamification (Pr < 0.01) between the origin of Robusta coffee and the length of fermentation of Robusta coffee and organoleptics which show a significant difference, namely the taste and texture are not significantly different, with this number showing that there is a high level. Origin of Robusta coffee and fermentation time with organoleptic tests which show the interaction of aroma and color by showing the highest numbers. In conclusion, there is no interaction between the origin of the robusta coffee location and the fermentation time on taste and texture, whereas there is an interaction between the origin of the robusta coffee and the fermentation time on the aroma and color.